2006
DOI: 10.1111/j.1365-2052.2006.01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the extent of linkage disequilibrium in commercial pig populations

Abstract: To evaluate the extent of linkage disequilibrium in domestic pigs, we genotyped 33 and 44 unrelated individuals from two commercial populations for 29 and five microsatellite markers located on chromosomes 15 and 2 respectively. A high proportion of marker pairs up to 40 cM apart exhibited significant linkage disequilibrium in both populations. Pair-wise r(2) values averaged between 0.15 and 0.50 (depending on chromosome and population) for markers <1 cM apart and declined to values of 0.05 for more distant sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 25 publications
2
26
1
Order By: Relevance
“…Herrero-Viedma et al, 2013) N e (LD) have large standard errors and are also sensitive to assumptions of constant N e (Corbin et al, 2012). Suggesting that the assumptions of the Wright equation are sometimes met in actual populations, Harmegnies et al (2006) found that in two commercial pig populations (each maintained at about ten boars and 250 to 300 sows) N e (LD) agreed 'reasonably well' with N e (Wright). Leroy et al (2013) found substantial variation between breeds in N e (DF).…”
Section: Discussionmentioning
confidence: 50%
“…Herrero-Viedma et al, 2013) N e (LD) have large standard errors and are also sensitive to assumptions of constant N e (Corbin et al, 2012). Suggesting that the assumptions of the Wright equation are sometimes met in actual populations, Harmegnies et al (2006) found that in two commercial pig populations (each maintained at about ten boars and 250 to 300 sows) N e (LD) agreed 'reasonably well' with N e (Wright). Leroy et al (2013) found substantial variation between breeds in N e (DF).…”
Section: Discussionmentioning
confidence: 50%
“…Founder effects in pigs can arise because of the economically driven extensive selection programmes, which reduce the effective population sizes strongly. In Belgian commercial pigs for example, the effective population size is diminished from thousands to less than 200 animals (Harmegnies et al, 2006). Selection for FUT1 A/A pigs implies that a positive selection for pigs deficient in the FUT1 gene is carried out.…”
Section: Discussionmentioning
confidence: 99%
“…LD mapping has been used extensively to identify genes for monogenic diseases in humans (Peltonen 2000). Contrary to the situation in humans, extensive LD over a long range was observed in dairy cattle, sheep, and pigs (Farnir et al 2000;Mcrae et al 2002;Tenesa et al 2003;Nsengimana et al 2004;Harmegnies et al 2006) because of limited effective population sizes. Thus, LD mapping in livestock, and in other populations with (historically) limited effective population sizes, might be effective using marker maps of more limited density than what is required for most human populations because of the extensive LD that is created by drift in populations of limited effective sizes (Terwilliger et al 1998;Farnir et al 2002).…”
mentioning
confidence: 99%